Analisis Pengaruh Kualitas WEB terhadap Peningkatan Harga Saham Perusahaan Manufaktur di Indonesia - Nur Rahmadi (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
This  research to analyze the influence of the quality WEB consisting of variable speed website, URL , keywords , internal links, media images , Content , meta description , outbound links, shocial sharing, title to the change or movement of stock prices in the manufacturing companies contained in Indonesia Stock Exchange , with a research model is quantitative and uses a descriptive analysis and multiple linear regression analysis . The findings in this study are seen based on the results of descriptive analysis , manufacturing companies have kuallitas web pretty good . Then based on the results of multiple linear regression analysis , showed that from the t-test , only the speed of a website that has a significant influence on stock price movements , while the other variables effect but not significant while simultaneously based on the results of all variables showed no significant effect